Avaliação do status sanitário dos criatórios de subsistência de suínos do município de Nossa Senhora do Livramento - MT para a promoção da sanidade da cadeia suinícola - Zarzenon, Marcos Antonio Patricio (2021)
In 2020, Brazil was on 4th ranking exporting 4 billion ton of pork and 6,7% was from Mato Grosso state. Among 2 million breeding herd 8.2 % is raised in Mato Grosso state. The maintenance of so large swineherd demand a well-planned, executed and evaluated swine health program. In this context, free life wild boar is a big challenge due to their prolific characteristic, absence of natural enemies and movement from the south to north of Brazilian country. The loss due to their presence in Brazil is related to environment destruction, social-economic and domestic swine herd health commitment. This research aimed to investigate the risk of wild boars to the livelihood farms of the Nossa Senhora do Livramento municipality due to their vulnerability to wild boars invasion and susceptibility to infectious diseases most of them identified. There were studied 80 among 1220 existing livelihood farms, a sample statistically significant. General characteristics of the investigated livelihood farms: farming less than 5 year; swine raised in close areas; feed with commercial food mixed with owner feed scraps; only one boar raised; 1- 9 breeders; and until 25 piglets. Perceptions of the livelihood farms owners about the risks due to wild boars: sparse information about legislation prohibiting feeding of their animals in landfill; they, usually don’t sight wild boar from their farms or in the landfill; they consider that it is possible crossbreed domestic swine’s with wild boars. In conclusion, we consider the importance of field education.